Literasi Digital di Era Pembelajaran Abad 21 - Fitriyani Fitriyani ; Arief Teguh Nugroho (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
This community service activity was carried out to provide socialization on the importance of understanding digital literacy in dealing with learning in the 21st century era as an effort to improve students' abilities through reading literacy activities so as to foster interests and talents in students from an early age as well as a literacy culture that is embedded in students. can affect the level of success and the ability of students to understand information analytically, critically, and reflectively. This community service activity was carried out at the Mekar Mukti 02 State Elementary School, North Cikarang. Some literacy support programs that can be applied in elementary schools include getting used to reading 15 minutes before learning has started, so that students' reading interest and reading skills increase and master better. Keywords: Digital Literacy, Socialization, 21st Century Learning